Quantitation of free and modified Alternaria mycotoxins in European food products by LC-MS/MS. (August 2019) - Puntscher, Hannes; Cobankovic, Iva; Marko, Doris; Warth, Benedikt
Abstract: Fungal secondary metabolites frequently contaminate agricultural products implying a potential toxicological concern for consumers. We report a food survey investigating 17 Alternaria mycotoxins in tomato sauce, sunflower seed oil and wheat flour. Matrix-dependent median concentrations of the most frequently studied toxins, namely alternariol (AOH), alternariol monomethyl ether (AME), tenuazonic acid, and tentoxin ranged between 1.2 and 6.6, 0.5–1.3, 66–161, and 0.1–0.5 ng/g. Additionally, the modified toxins AOH-3-sulfate (up to 2.1 ng/g) and AME-3-sulfate (up to 17.5 ng/g) were detected in 9% and 34% of tomato sauces accounting for 7–100% of their parent toxin concentrations. The barely studied perylene quinones altertoxin I and alterperylenol were determined in all matrices with concentrations of up to 6 and 48 ng/g, respectively. The contamination patterns of sample subgroups were compared considering multiple factors (e.g. country of origin, type of agriculture, vendor, food processing). Samples from organic agriculture showed comparably higher median and maximum concentrations of the investigated Alternaria toxins, but also national and vendor-specific (supermarket chains vs. online stores) quality requirements for agricultural crops and food processing in the case of sunflower seed oils seem to affect the Alternaria toxin contamination patterns in food commodities. Overall, the presented study contributes comprehensive Alternaria toxin occurrence data which is necessary for future risk assessments evaluating potentially caused health concerns for consumers. Highlights: Up to nine of 17 Alternaria toxins were determined in food samples. Detected levels of modified toxins indicate their relevance for risk assessment. Barely studied perylene quinones determined at considerable concentrations. Organic agriculture does not directly correlate with mycotoxin contamination.